Options for treating postherpetic neuralgia in the medically complicated patient - Bruckenthal P; Barkin RL (Dove Medical Press, 2013)
Patricia Bruckenthal,1 Robert L Barkin2,31Department of Graduate Studies in Advanced Practice Nursing, Stony Brook University School of Nursing, Stony Brook, NY, USA; 2Department of Anesthesiology, Family Medicine, and Pharmacology, Rush University Medical College, Chicago, IL, USA; 3Department of Anesthesiology, Northshore University Health System Pain Centers, Skokie and Evanston Hospitals, Skokie and Evanston, IL, USAAbstract: Patients with postherpetic neuralgia (PHN) are often of advanced age or immunocompromised and likely to have ≥1 comorbid medical condition for which they receive ≥1 medication (polypharmacy). Comorbidities affecting renal or hepatic function can alter pharmacokinetics, thereby impacting the efficacy or tolerability of PHN analgesic therapies. Cardiovascular, cerebrovascular, or psychiatric comorbidities may increase patient vulnerability to potential adverse events associated with some PHN analgesic therapies. Because PHN is a localized condition, localized therapy with a topical analgesic (lidocaine patch 5% and capsaicin 8% patch or cream) may provide adequate efficacy while mitigating the risk of systemic adverse events compared with oral analgesics (eg, tricyclic antidepressants, anticonvulsants, opioids). However, combined therapy with a topical and an oral analgesic or with >1 oral analgesic may be needed for optimal pain management in some patients. This review summarizes how comorbidities and concomitant medications should be taken into account when selecting among available pharmacotherapies for PHN and provides recommendations for the selection of therapies that will provide analgesia while minimizing the risk of adverse events.Keywords: calcium channel α2-δ ligand, comorbidities, lidocaine patch, polypharmacy, postherpetic neuralgia, TCA